Molecular and transcriptional regulation of the interleukin-10 gene: Implications of the -1082 G/A promoter polymorphism on the immune response in pulmonary tuberculosis - Rieke Dwi Ramadhany; Desi Oktariana; Kemas Yakub Rahadiyanto (Institute of Computer Science (IOCS), 2026)
Background: Host immune responses critically determine tuberculosis outcomes. Although the interleukin-10 (IL-10) -1082 G/A promoter polymorphism alters IL-10 expression and pulmonary tuberculosis susceptibility, global studies report conflicting findings that lack a comprehensive molecular synthesis. Objective: This review critically evaluates IL-10 molecular regulation and the immunological and clinical implications of the -1082 G/A polymorphism in pulmonary tuberculosis. Methods: A narrative literature review utilized PubMed, ScienceDirect, and Google Scholar (2008–2026). Employing a structured literature selection flowchart and the Joanna Briggs Institute (JBI) Critical Appraisal tools for quality assessment, 55 high-quality articles were ultimately selected and synthesized narratively. Results: The G allele exhibits greater affinity for the Sp1 transcription factor, increasing IL-10 expression. This hyper-secretion suppresses macrophage activation and Th1-mediated immunity via the JAK/STAT pathway. Crucially, susceptibility differences among populations are heavily influenced by linkage disequilibrium, ethnic genetic diversity, epigenetic regulation, and gene–environment interactions. Conclusion: This review provides an integrated perspective linking the IL-10 promoter polymorphism with immune regulation, highlighting its potential as a predictive biomarker for precision medicine and risk stratification in vulnerable demographics. Large-scale, multi-ethnic longitudinal studies integrating genetic and epigenetic analyses are recommended.